Phenotype variability and basic morphological characteristics of the Aksaray Malakli dog population in Turkey - Urošević, Milivoje, veterinar (Array, 2021)
The Turkish Mastiff or Aksaray Malakli Dog is a Turkish dog breed not yet officially recognized by the world canine organization - Fédération Cynologique Internationale (FCI). To achieve recognition, more research and analysis of the morphometric parameters of this breed are required. Previous research on this breed presented the average values of certain morphological parameters. Measurement results of 20 morphometric parameters showed that there are statistically significant differences in body structure between males and females. Such results are significant for setting the official breed standard in which the proportions of the body characteristic of this breed should be emphasized.